Fact searching in investigative reporting in indonesia: A case study of tempo and gatra magazines - Kurnia S.S.; Firmansyah; Kuswarno E.; Siti Suriani Othman (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by Scopus